Implementasi Media Video dalam Meningkatkan Motivasi Belajar Pendidikan Pancasila dan Kewarganegaraan pada Peserta Didik Kelas XI IPS di SMA Negeri 1 Lunang - Andra, Andra; Jaenam, Jaenam; Rahmat, Indra (Asian Journal of Early Childhood and Elementary Education, 2023)
The background of this research is to improve the quality of student learning and student achievement in Pancasila and civic education lessons by using video media that can be used to channel messages so that it can stimulate thoughts, feelings, concerns, and interests, students' attention so that students' motivation in learning increases. This study aims to: 1) Describe the teacher's process in implementing video media in Civics learning. 2) Knowing the obstacles faced by teachers in implementing video media in Civics learning 3). Describes students' motivation in using video media in Civics learning. This study uses behavioristic theory, this theory examines human behavior. The type of research used is descriptive with a qualitative approach. The informants in this study were teachers of Pancasila and Citizenship Education at SMAN 1 Lunang, Deputy Curriculum at SMAN 1 Lunang and students from class XI Social Sciences at SMAN I at Lunang. Data collection techniques in this study are observation, interviews and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of the research that has been done, found: 1) In implementing video media in Civics learning, the teacher first looks for learning videos on YouTube and then adjusts them to the lesson plans and modules, after that the teacher plays the videos in class according to the appropriate methods and procedures. So as to produce effective, efficient learning and increase student motivation. This is because the enthusiasm of students in learning increases. 2) Obstacles that are often experienced in using video media are teachers who have difficulty managing learning time with the duration of the video, with the duration of lesson hours. 3) The motivation of students in using video media in Civics learning is able to make students' attention focus on learning so that all questions given by the teacher are answered by students.